KOMUNIKASI INTERPERSONAL DRIVER SHOPEEFOOD DENGAN KONSUMEN - Hidayat, Taufik; Sekar Wangi, Maya; Itasari, Andri Astuti (Solidaritas, 2024)
The food delivery service industry is currently experiencing increasingly fierce competition. This has triggered an increase in the use of digital platforms due to the availability of various alternative choices for consumers, thus requiring companies to be able to provide superior service attributes compared to their competitors. ShopeeFood as a new service provides various benefits, but its weakness is misunderstandings caused by online communication or not being connected directly when ordering food. Therefore, ShopeeFood drivers as representatives seem to have to take users' attention again, namely through interpersonal communication interactions aimed at fulfilling user satisfaction and loyalty. Consumer satisfaction is one of the important factors that must be considered in order to satisfy consumers. This research aims to determine the interpersonal communication carried out by shopeefood drivers with consumers to get good feedback. This research uses descriptive qualitative methods, researchers also use Miles and Huberman data analysis techniques, namely data reduction, data presentation, and drawing conclusions. Researchers also used purposive sampling techniques to determine informants who were experts and whose statements could be trusted to be used as data sources. The informants in this research were Solobaru shopeefood drivers and shopeefood consumers. The results of this research were obtained using interpersonal communication theory with a humanistic approach from Joseph Devito which consists of five aspects, namely, openness, empathy, supportive attitude, positive attitude, and equality. The interpersonal communication between shopeefood drivers and consumers is very good when shopeefood orders are in progress. So that shopeefood drivers and consumers provide mutual support and respect to minimize debate, good communication is very necessary to get good feedback from shopeefood consumers and add stars to shopeefood driver profiles. Keywords: Interpersonal communication, Shopeefood drivers, Shopeefood consumers